Early life history stages of the family Carangidae in the Eastern Adriatic - Dulčić, Jakov (Annales. Series historia naturalis, 1998)
Use of early life history stages in systematic and ecological studies of fish has increased in recent years. It is now recognized that eggs and larvae present a wide array of characters that are largely independent of adult characters and, as such, suitable for a taxonomic analysis. On the other hand, fisheries recruitment stuides focus on the survival of eggs and larvae as the most important factor influencing variations in population abundance. A requistie to these studies is detailed information on the appearance of fish eggs and larvae in order to identify them in plankton samples...
Keywords: Carangidae; razvojni stadiji; ribe; Vzhodni Jadran